ifo DSGE model 2.0 - Radek Šauer (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2022)
This documentation concisely describes the dynamic stochastic general-equilibrium model that the ifo Institute currently uses for simulations and business-cycle analysis. The model consists of three countries and contains a wide range of rigidities. The model is regularly estimated by quarterly macroeconomic data.
Keywords: E17; 330; DSGE; simulations; forecasting; business-cycle analysis